2022
DOI: 10.4103/joco.joco_337_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of refractive errors among ophthalmic patients in Madang Province, Papua New Guinea

Abstract: Purpose: To assess the prevalence and distribution of refractive errors in Madang Province, Papua New Guinea (PNG). Methods: A retrospective hospital-based study was conducted at Madang Provincial Hospital Eye Clinic. It is a free eye clinic and spectacle costs are further subsidized by a nongovernmental organization. Nonprobability purposive sampling was used to retrieve patients' records at the eye clinic from January to December 2016. Only demographic and clinic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In Papua New Guinea (PNG), a rapid assessment of avoidable blindness (RAAB) was carried out in 2017 but the study focused mainly on the causes of visual impairment (VI) and blindness (presenting visual acuity <6/12) in the older population (aged 50 years and older) ( 14 ). Contrariwise, studies have indicated that there are potentially blinding conditions that do not present significant ocular or visual symptoms in the initial stages ( 11 , 15 ), and PNG is not immune to such potential causes of visual impairment ( 16 , 17 ). Therefore, the findings of the RAAB are limited in terms of the general presentation of eye disorders in the country.…”
Section: Introductionmentioning
confidence: 99%
“…In Papua New Guinea (PNG), a rapid assessment of avoidable blindness (RAAB) was carried out in 2017 but the study focused mainly on the causes of visual impairment (VI) and blindness (presenting visual acuity <6/12) in the older population (aged 50 years and older) ( 14 ). Contrariwise, studies have indicated that there are potentially blinding conditions that do not present significant ocular or visual symptoms in the initial stages ( 11 , 15 ), and PNG is not immune to such potential causes of visual impairment ( 16 , 17 ). Therefore, the findings of the RAAB are limited in terms of the general presentation of eye disorders in the country.…”
Section: Introductionmentioning
confidence: 99%